The development of somatic embryos of sago palm (Metroxylon sagu Rottb.) on solid media *) Perkembangan embrio somatik tanaman sagu (Metroxylon sagu Rottb.) pada medium padat - Imron RIYADI; J.S. TAHARDI TAHARDI; . SUMARYONO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2005)
SummarySago palm (Metroxylon sagu Rottb.) isusually propagated vegetatively by suckers.However, the limited availability of uniformsuckers is a major obstacle in the establishmentof cultivated sago plantations. Tissue culture hasthe potential for large-scale mass clonalpropagation of superior genotypes of sago palm.In vitro culture of sago palm has been establishedthrough somatic embryogenesis. Embryogeniccallus derived from shoot apical tissue of youngsuckers was cultured on a modified Murashigeand Skoog (MMS) medium containing 30 g/Lsucrose, 2 g/L Gelrite, 1 g/L activated charcoal,5.0 mg/L 2,4-D, and 0.1 mg/L kinetin to inducesomatic embryos. Callus clumps formed somaticembryos within four weeks. In the subsequentculture, approximately 0.3 g initial globularcallus grown on MMS medium containing 1.0mg/L kinetin, 0.01 mg/L ABA and 0.1 mg/L GA 3produced 140 to 200 somatic embryos at differentdevelopmental stages four weeks later. All stagesof developing embryos with different sizesand colors were present at any one time ofculture. Secondary (repetitive) somatic embryo-genesis was also found in the culture.Transferring of the mature stage of somaticembryos to solid media with half-strength macro salts and with sucrose at concentration of 20 or 30 g/L without growth regulators led to the development of normal plantlets.RingkasanTanaman sagu (Metroxylon sagu Rottb.)biasanya diperbanyak secara vegetatif dengantunas anakan. Namun, terbatasnya ketersediaantunas anakan yang seragam merupakanhambatan utama dalam pembukaan perkebunansagu. Teknologi kultur jaringan mempunyaipotensi untuk perbanyakan klonal tanaman saguunggul dalam skala besar. Kultur in vitrotanaman sagu telah dikembangkan melaluiembriogenesis somatik. Kalus embriogenik yangberasal dari eksplan pucuk tunas anakandikulturkan pada medium modifikasi Murashigedan Skoog (MMS) dengan sukrosa 30 g/L,Gelrite 2 g/L, arang aktif 1 g/L, 2,4-D 5 mg/Ldan kinetin 0,1 mg/L untuk menginduksi embriosomatik. Kalus membentuk embrio somatikdalam waktu empat minggu. Dalam kulturberikutnya, dari kurang-lebih 0,3 g embrio faseglobuler yang dikulturkan pada medium MMSdengan kinetin 1,0 mg/L, ABA 0,01 mg/L danGA 3 0,1 mg/L menghasilkan 140 sampai 200embrio somatik dengan fase perkembangan yangberbeda-beda. Embrio somatik dalam semuafase perkembangan dengan ukuran dan warnayang berbeda-beda ditemukan setiap saat dalamkultur. Di samping itu, embriogenesis somatiksekunder (berulang) juga terjadi dalam kultursagu. Embrio somatik fase dewasa biladipindah ke medium padat dengan garam makrosetengah konsentrasi dan sukrosa padakonsentrasi 20 atau 30 g/L tanpa zat pengaturtumbuh akan menjadi planlet normal.